2017
DOI: 10.1155/2017/1203269
|View full text |Cite
|
Sign up to set email alerts
|

Intraocular Pressure, Axial Length, and Refractive Changes after Phacoemulsification and Trabeculectomy for Open-Angle Glaucoma

Abstract: Purpose To compare changes in intraocular pressure (IOP), axial eye length (AEL), and refractive outcome in primary open-angle glaucoma patients undergoing cataract surgery and trabeculectomy in dependence of the sequence of surgeries. Materials and Methods We retrospectively analysed 48 eyes. The changes in refraction, intraocular pressure, and axial eye length were analysed after surgery. In group A (21 subjects), phacoemulsification was performed before trabeculectomy, and in group B (27 subjects), trabecul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 30 publications
(26 reference statements)
0
8
0
1
Order By: Relevance
“…In fact, multivariate analysis has shown that greater DIOP rather than lower postoperative IOP is a significant prognostic factor for choroidal detachment, suggesting that the gap between pre-and postoperative IOPs increases the occurrence of choroidal detachment rather than postoperative hypotony, which may be explained by the change in ocular shape. Several reports have shown that IOP reduction causes axial length shortening after trabeculectomy [11][12][13][14][15]. The structural change in eyeball shape due to greater DIOP might have increased fluid inflow into the suprachoroidal space.…”
Section: Discussionmentioning
confidence: 99%
“…In fact, multivariate analysis has shown that greater DIOP rather than lower postoperative IOP is a significant prognostic factor for choroidal detachment, suggesting that the gap between pre-and postoperative IOPs increases the occurrence of choroidal detachment rather than postoperative hypotony, which may be explained by the change in ocular shape. Several reports have shown that IOP reduction causes axial length shortening after trabeculectomy [11][12][13][14][15]. The structural change in eyeball shape due to greater DIOP might have increased fluid inflow into the suprachoroidal space.…”
Section: Discussionmentioning
confidence: 99%
“…Also, there are various reports describing IOP reduction after trabeculectomy that may cause AL shortening. 9,10 However, there are no reports concerning the effects on the ocular biometrics after glaucoma filtering surgery with a mini shunt device.…”
Section: Resultsmentioning
confidence: 99%
“…Previous studies have shown that axial length decreases when trabeculectomy is performed in patients with high myopia [10][11][12][13], and animal studies have also reported that axial length decreases when intraocular pressure (IOP) is lowered [14][15][16]. Another study revealed that IOP and increased axial length affected the progression of myopic retinoschisis [17].…”
Section: Original Articlementioning
confidence: 99%